Trajectories of intimate partner violence: from psychological and physical abuse to homicide - Pereira, Paula Sismeiro (2018)
The present study analyses dynamics of intimate partner violence from the male poínt of view. Continuity or qualitative discontinuity between abusive behaviour and homicide and unity versus diyersity of homicidal behaviour will be disccussed in a contextualized approach considering the dynamics of couple relationships and several male features. This study has a quantitative and qualitative methodology using several scales to assess personality, attachment to parents and to romantic partners and a semi-structured interview specially conceived for this research. Some of the main dimensions explored through male narratives were courtship, frequency and severity of physical and psychological violence during couple relationships, early childhood experiences, attachment to female partner, social relationships beyond family members and description of abusive and homicidal behaviour. Our participants are male adults inmates condemned for violence or homicide against their female partner: 15 men arrested for homicide or attempted homicide of their partner and 5 men arrested for violence against their partner. A content analysis from the interview transcripts was conducted in order to explore dimensions presented above and to identify themes associated to abusive and homicidal acts. A sequential analysis was conducted to assess male conceptualization of violent or homicidal episodes. Three trajectories emerge from those analyses. One of them is a trajectory of abusive behaviour that usually does not end in homicide and two other trajectories leading to homicide. Those trajectories will be discussed considering the dimensions explored. Major implications for intervention will be debated.